Universal scaling laws of keyhole stability and porosity in 3D printing of metals - Zhengtao Gan (Nature Portfolio, 2021)
Identifying scaling laws in metal 3D printing is key to process optimization and materials development. Here the authors report scaling laws to quantify correlation between process parameters, keyhole stability and pore formation by high-speed synchrotron X-ray imaging and multiphysics modeling.